2020
DOI: 10.5860/crl.81.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Reinventing Ourselves: New and Emerging Roles of Academic Librarians in Canadian Research-Intensive Universities

Abstract: The academic library profession is being redefined by the shifting research and scholarly landscape, the transformation in higher education, and advances in technology. A survey of librarians working in Canada's research-intensive universities was conducted to explore new and emerging roles. This study focuses on librarians' activities in: Research Support, Teaching and Learning, Digital Scholarship, User Experience, and Scholarly Communication. It addresses the scope and nature of the new roles, the skills re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 46 publications
0
31
0
2
Order By: Relevance
“…Employers are critical partners whose active involvement contributes positively to the continuing professional development of library and information professionals (Australian Library and Information Association, 2019). Ducas et al (2020) argue that it is imperative for academic libraries to firmly support the professional development efforts of their librarians to develop expertise for the new roles, such as data management and online teaching. Employers have a key responsibility to provide opportunities for learning that support library and information professionals to enhance their knowledge and skills throughout their career in order to meet the changing needs of their clients, employers and society (Australian Library and Information Association, 2019).…”
Section: Academic Libraries As Learning Organisationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Employers are critical partners whose active involvement contributes positively to the continuing professional development of library and information professionals (Australian Library and Information Association, 2019). Ducas et al (2020) argue that it is imperative for academic libraries to firmly support the professional development efforts of their librarians to develop expertise for the new roles, such as data management and online teaching. Employers have a key responsibility to provide opportunities for learning that support library and information professionals to enhance their knowledge and skills throughout their career in order to meet the changing needs of their clients, employers and society (Australian Library and Information Association, 2019).…”
Section: Academic Libraries As Learning Organisationsmentioning
confidence: 99%
“…Learning by doing, experimenting, and playing with tools and ideas engages staff in meaningful and transformative learning (Lawler, 2016). A study of Canadian academic librarians found that survey respondents acquired skills primarily through individual activities of professional work experience (learning on the job) and self-teaching, followed by external professional development activities and attending workshops or seminars within their library (Ducas et al, 2020). In Australia, the University of Wollongong Library developed a successful program to build library staff's digital literacy skills using the principles of personalisation, flexibility, learning agency and self-directed learning (Shalavin, 2018).…”
Section: Academic Libraries As Learning Organisationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond their work troubleshooting technology at the reference desk, librarians also have extensive experience with developing and implementing instruction programs. Ducas et al (2020) found that a majority of librarians surveyed participated in some vein of "Teach and Learning" services. The core of this work is often with first-year students, providing library and research orientations during many of the 100 level 3 courses or first-year seminars.…”
Section: Role Of Librarian Collaboration With Summer 2020 Pilotmentioning
confidence: 99%
“…41 Indeed, the picture drawn by this research raises relevant implications and opportunities for academic librarians, encouraging their involvement in the ever-vibrant life cycle of IL in higher education. 42 In this age of disinformation and fake news, and given the dynamic needs for academic training, fostering IL for the entire university community should be a priority. For this reason, many universities are promoting institutional plans to address the new education challenges posed by the current context, although most of them focus on the digital transformation of institutions.…”
Section: Recommendations and Implications For Academic Librariesmentioning
confidence: 99%